2018
DOI: 10.1021/acs.estlett.8b00215
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Uranium Contamination of Groundwater Resources in India

Abstract: Groundwater overexploitation has caused massive groundwater depletion and raised concerns for water and food security in India. Groundwater in India also suffers from multiple water quality issues such as arsenic and fluoride contamination that pose human health risks. Here we report new data showing that the occurrence in uranium in Indian groundwater is an emerging and widespread phenomenon. We present compiled data on groundwater uranium from 16 Indian states and new data from 324 wells in the states of Raj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 36 publications
6
90
1
Order By: Relevance
“…Weekly ethanol additions stimulated microbial activities and the reduction of soluble-and solid-phase U (VI) to sparingly soluble U(IV), with aqueous U concentrations falling to levels below the US 4 EPA drinking water standard (0.03 mg/L) (Wu et al, 2007). The uranium reduction reaction can be described as: UO2 2+ + 2 e -→ UO2(s) (ΔGº' = -43.2 kJ/eq) 1Subsequent results demonstrated that the reduced/immobilized uranium was stable in the absence of DO and nitrate under anaerobic conditions, but susceptible to oxidization and remobilization when dissolved oxygen (Wu et al, 2007) and nitrate (Wu et al, 2010) were injected into the treatment zone, which is consistent with the observation of increased uranium concentrations in the presence of the oxidant nitrate in other studies (Coyte et al, 2018;Nolan and Weber, 2015;Senko et al, 2002Senko et al, , 2005b. After December 2008, the controlled field tests stopped and contaminated groundwater, including the oxidants nitrate and oxygen, were allowed to reinvade the treatment zone (Li et al, 2018).…”
Section: Introductionsupporting
confidence: 86%
“…Weekly ethanol additions stimulated microbial activities and the reduction of soluble-and solid-phase U (VI) to sparingly soluble U(IV), with aqueous U concentrations falling to levels below the US 4 EPA drinking water standard (0.03 mg/L) (Wu et al, 2007). The uranium reduction reaction can be described as: UO2 2+ + 2 e -→ UO2(s) (ΔGº' = -43.2 kJ/eq) 1Subsequent results demonstrated that the reduced/immobilized uranium was stable in the absence of DO and nitrate under anaerobic conditions, but susceptible to oxidization and remobilization when dissolved oxygen (Wu et al, 2007) and nitrate (Wu et al, 2010) were injected into the treatment zone, which is consistent with the observation of increased uranium concentrations in the presence of the oxidant nitrate in other studies (Coyte et al, 2018;Nolan and Weber, 2015;Senko et al, 2002Senko et al, , 2005b. After December 2008, the controlled field tests stopped and contaminated groundwater, including the oxidants nitrate and oxygen, were allowed to reinvade the treatment zone (Li et al, 2018).…”
Section: Introductionsupporting
confidence: 86%
“…Not only are average concentrations high, but in areas with hard rock aquifers, nitrate contamination is found at staggering depths of more than 350 meters, showing that even deep groundwater is not safe from contamination (Biswas and Jamwal 2017). Furthermore, the presence of nitrates in groundwater enhances the mobilization of other deadly pollutants such as uranium, compounding the threat of groundwater pollution (Coyte et al 2018).…”
Section: Box 22: Nitrogen In Waters Runs Deepmentioning
confidence: 99%
“…Groundwater depth is shallow and prone to leaching of elements because of precipitation. U concentration is observed high in shallow groundwater of semi-arid (Coyte et al 2018) and arid region (Burow et al 2017) due to leaching. The Khetri belt lies in the semi-arid region with shallow groundwater.…”
Section: Weatheringmentioning
confidence: 99%